The photovoltaic application and optics of ZnO-CdO and ZnO-NiO nanocomposite binary system - Soylu, M.; Al-Sehemi, Abdullah G.; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2022)
ZnO/CdO and ZnO/NiO nanocomposite (NC) thin films were synthesized using co-precipitation by the sol-gel method. ZnO/CdO and ZnO/NiO are varied as volume ratio (ZnO/CdO: 2/1 mL and 2.5/0.5 mL; ZnO/NiO: 2/1 mL and 2.5/0.5 mL). The optical characteristics were analytically investigated using the transmittance, absorbance and reflectance data. While the band gap of the alloyed ZnO increases with decreasing CdO, it decreases with decreasing NiO. This is in line with the fact that the band gap of CdO is smaller than ZnO and the band gap of NiO is greater than that of ZnO. Such systems behave as semiconductor demonstrating the band gap engineering. ZnO-CdO/p-Si and ZnO-NiO/p-Si heterojunctions exhibit rectifying behavior and photodiode property, indicating an increase in current with increasing illumination in the case of reverse bias. The quantity-dependent photoresponse properties were examined using the current-voltage (I-V), transient photocurrent (I-t) and transient photocapacitance (C-t) measurements. Time-resolved photoresponse reveals that the photocurrent is related to the assumption of continuously distributed trap states in the band gap.
Keywords: Nanocomposite; Volume ratio; Electrical properties